Yüksek alaşımlı ve paslanmaz çeliklerin sert plaketli takımlarla tornalama prosesinin kesme kuvvetleri, kesme gücü ve özgül kesme enerjisi bakımından incelenmesi - Absadykov, Bakhyt (Fen Bilimleri Enstitüsü, 1997)
Tezde sunulan araştırma talaş kaldırma prosesinin rasyonaleştirme çalışmaları ile ilgilidir. Buna göre tezde esasen sert plaketli takımla işlenen yüksek alaşımlı ve paslanmaz (ısıya dayanıklı) çeliklerin:. Kesme kuvvetleri ve kesme gücü;. özgül kesme enerjisi ve. Harcanan motor enerjisi ile talaş kaldırma faktörlerin kontrolü incelenmiştir. Tez teorik-deneysel niteliğini taşımaktadır. Tezin ortaya koyduğu en önemli işlemler ve sonuçlar şu şekilde sıralanabilir.. Deney sonuçların literatürde verilen bağıntılarla karşılaştırılmasında oldukça büyük farklıklar olduğu görülmüş ve buna göre kesme kuvvetleri ve kesme gücü için yeni bağıntılar bulunmuştur.. Talaş kaldırma prosesinin değerlendirilmesi ve optimizasyon işleminde esas alınması için özgül kesme enerjisi kriteri önerilmiş ve bu kriter her yönü ile analize edilmiştir.. Tezde önerilen ve pratik bakımından önemli olan bir başka husus tezgah motor enerjisinin kontrol sistemidir. Bu kontrol sistemi; tezgahın harcadığı enerjiyi, talaş kaldırma prosesini oluşturan kesme kuvvetlerin değerini, değişmelerini, kesme gücünün değerini, takım kırılmasını, takım aşınmasını kontrol etmekte ve ayrıca malzemelerin işlenme kabiliyetlerini tayin etmektedir.. Fiziksel olarak talaş kaldırma prosesini etkileyen en önemli olay malzemelerin plastik şekil-değiştirmeleridir Bu olay talaş kaldırma prosesini tamamen yönlendirmekte ve bazı çelişkili sonuçları açıklamaktadır. Bu hususla ilgili bir başka önemli sonuç, talaş kaldırma sırasında, kesme şartlarına bağlı olarak malzemelerin plastik şekil-değiştirme davranışlarının değişmesidir.. Plastik şekil-değiştirmelerle ilgili talaş kaldırma prosesini önemli şeklinde etkileyen bir başka olay ağız birikintisidir. Bu olay talaş kaldırma prosesini çift yönlü yani hem olumlu, hem de olumsuz şeklinde etkilemektedir.

The rationalisation of chip formation process which had been beginning in 1900 years by Taylor and had been continued in 1940's by Merchant is developing very intensively at the last time. The most important matter in the rationalisation is a selection of cutting parameters on the base of scientific and research results. Scientific results may be given in analytical or optimisation forms. These results are used more and more easily in computer programmes, CAM systems and NC programmes at the our time. Therefore at first, rationalisation is a reason for increasing of productivity and product quality and for reducing production costs. However influence of cutting factors on chip formation isn't known so far certainly. The most important reason is that very complicated an operation with solid mechanics and mechanical energy; elasticity and plasticity, breaking, friction, wear and lubrication, thermal energy formation, transferring for chip formation process. The result of it's having a less rational knowledge's about high alloy and stainless steels using in the conditions of high temperature and loads. The researches in this thesis explain rationalisation of chip formation process. Therefore to have been examined following:. Cutting forces and cutting power;. Specific cutting energy and. Chip formation controls with expending lathe's motor energy. The chapter One of the thesis named as "Significance of Chip Formation and Topic of Thesis" is explaining the significance of chip formation and the methods of developments chip formation process by scientists. Explanations of chip formation process are divided into two groups. First group is studying a theory of thin shear plane and second xx group is studying a theory of thick shear zone especially in that chapter the topic of the thesis has been explained and concentrated attention on chosen questions. In chapter Two was made a physical and theoretical analysis of chip formation process. There the chip formation models were researched and explored necessary postulates. Taking into consideration significance of shape-changing in chip formation process, was given information about plastic shape-changing and were researched a slip criterion's and slip lines field theory. Afterwards analysis of Merchant's thin plane theory, which is very important for chip formation process development was done. There were researched cutting tensile and cutting forces, cutting ratio and cutting angle, slip shape-changing, chip formation speed, slip shape- changing speed, friction's in chip formations and sticky friction, dispersion of chips torsion on tools and were given necessary equations and correlation's. The cutting angle value and spent energy of chip formation process were analysed with the help of criterion of minimum energy. In the same chapter of the thin plane theory was researched and written criticising articles. Afterwards slip line field models of thick zone theory were analysed and results were compared with the results of the model of thin plane theory. In chapter Three analytical and experimental determinations of cutting forces are explored. Here, the comparison of the chip formation models with the true turning has been made, and, leaning on thin plane theory and oblique cutting models, equations for cutting forces had been determined and shown that equations can't be using at real conditions. Afterwards, theoretical proportions, based on true turning models had been found. This proportions had been done the basic formulas for experimental working. Also basing on halt-analytical methods, cutting forces equations were given for true turning. This part of the Chapter Three is concerned with the up-to-date information on using dynamometers, their varieties and methods of measurement of cutting forces. Information on experiment, experimental factors and devices tuning are presented in chapter Four. In that chapter are explained using lathe, measuring devices, dynamometer for measuring forces and working principles. Information on material, tools, tools geometry, cutting speeds, feeds, layer thickness are given in chapter Four too. XXI 38XH3MA (38HN3MA), 14X17H2 (14H17N2) and 20XH(20HN) steels (GOST 5632-72)1 were used in experiment. How a model were used the round bars with parameters: diameter D=90 mm; length L=600 mm. The tools that used in experiments are tools with tungsten carbide insert BK-8 (VK-8) (GOST 3882-74) with normal rake angle y=7° and y=-7°. In the end of chapter necessary explanation about calibrations of devices is given. Direction of experiments, experimental data are given in chapter Five. The experimental results on cutting forces and cutting powers are shown on tables (from table A.1 to table A.6) and in accordance with that results, cutting forces-layer thickness (from fig. A. 1a to fig. A. 10a) and cutting forces- feed (from fig. A.1 1a to fig. A.20a) diagrams had been drawn. Basing on theoretical formulas for high alloys and stainless steels, cutting forces-layer thickness (from fig. A. 1b to fig. A. 10b) and cutting forces- feed (from fig. A.1 1b to fig. A.20b) theoretical diagrams had been drawn. Theoretical and experimental data were compared and the differences between theirs from 25% to 104% are determined, moving from that results, the criterion of minimum slip coefficients has been applied to experimental data for every material. An accordance with that criterion were found the new correlation (5.12...5.17). In chapter Six is explored and determined specific cutting energy, and after analysed it were found correlation's. (6.1 9...6.21). The analysis of that correlation's, from layer thickness (a), feed (s), cutting speed (v) and materials hardness (HB) was made, and that analysis defines that specific cutting energy on definite feed receives the minimum significance. A few words about layer thickness and cutting speed: if a layer thickness is increasing, the specific cutting energy will be decreased, and if cutting speed is increasing, the specific cutting energy will be decreased too. Afterward, in accordance with analysis, shown that optimisation of chip formation can be doing with the specific cutting criterion. For that reason, using limit significance's for cutting forces, expending powers, productivity, tool life and cutting factors had been written optimisation equations and had been drawn diagrams (Fig. B1...Fig.B6). 1 GOST 5632-72 - Russian Institute of Standards XXII The chapter Seven showing the process direction of control making with motors expending energy for cutting forces, cutting power, tool wear. For that matter, the experiments have been done and details of that direction have been explained, separately, the new method of determine materials machine ability with the help of motors expending energy is described in the same chapter. This method had been applied to steels given in thesis and results are shown in the table 7.1. In the chapter Eight models thesis generalisation and the chapter Nine contains conclusions and proposes. The most important results which makes in that chapters have been written below: 1. The most important result of experiments is a plastic form-changing of a material which effects on the chip formation process. 2. The principle of the plastic form-changing that if a long time or high energy have been spending, cutting forces will have increased. If spent time is a less, cutting forces will have decreased. In opposite if a hardness or a tensile resistance have been increasing, cutting forces will have increased, because stresses will have increased too. On account of that reason if a hardness or a tensile resistance will have taken only; hardness or tensile resistance while increasing, cutting forces increases too. 3. The another important result of thesis it's a changing of materials form-changing behaviour in consequence of cutting factors. If layer thickness is a large, a plastic form will be changing less; but in the case of a thin layer thickness the plastic form will be changing considerably. Therefore if having a large layer thickness the changes from cutting forces depends on main formulas; but if using a thin layer thickness it can to give a contradictory results. Here, the materials plastic form-changing capability means an important role. 4. In the chip formation fields, that peculiarity of plastic form-changing which effected on cutting forces, cutting power and technological solution can be taken into consideration. The biggest form-changing is taking place in spot contact of the cutting edge of tool with material. It's a pressure form- changing. Afterward, a chip will be begun flow from dolls face. It's a bending form-changing. 5. In metal cutting, at some intermediate speed, shearing takes place along a nose of stationary material attached to the tool face. This so-called XXIII built-up edge acts like an extension of the tool: Shear takes place along the boundary of the built-up edge; hence the effective rake angle becomes quite large and the energy consumption drops. However, an advantage is paid: dimensional control is last and, because the built-up edge becomes periodically, it leaves occasional lumps of metal and damaging cracks behind, and the surface finish is poor. 6. In that thesis far realising the value of chip formation process, specific cutting energy criterion is very appropriate. That criterion more better express lathes energy expending in conditions of chip formation. When an energy are examined only, expending energy cannot elucidate economic value of that process. And examine a volume of chip formation only, its cannot elucidate economical value of that process too. If taken this two factors with the specific energy meaning together (e=E/Vt) positive results can be given. If a specific energy will be increasing, a chip formation value will be increasing too; and a specific energies decreasing is a chip formations value decreasing too. 7. The another matter which has been proposed in the thesis is a control system of lathe motors energy The function of that control system is expressing of lathers expending energy, cutting forces data of chip formation, cutting power data, tools breaking, tools wear and working capability of materials. In this conditions can be given economic value of chip formation. Overloading of cutting forces is arisen of tools breaking and wearing. Especially materials working capability can be determined very quickly. 8. Cutting forces, cutting power and specific cutting energy proportions were researched in the Thesis on the base of theoretical and experimental data. There are using in the following cases:. In the rational selections of cutting factors.. In the optimisation works of cutting factors.. At the designing of new lathes. x
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1997
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 1997
Keywords: Makine Mühendisliği; Kesme kuvveti; Paslanmaz çelik; Tornalama; Mechanical Engineering; Cutting force; Stainless steel; Turning